2014
DOI: 10.3389/fnins.2014.00129
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of phosphodiesterase 4 reduces ethanol intake and preference in C57BL/6J mice

Abstract: Some anti-inflammatory medications reduce alcohol consumption in rodent models. Inhibition of phosphodiesterases (PDE) increases cAMP and reduces inflammatory signaling. Rolipram, an inhibitor of PDE4, markedly reduced ethanol intake and preference in mice and reduced ethanol seeking and consumption in alcohol-preferring fawn-hooded rats (Hu et al., 2011; Wen et al., 2012). To determine if these effects were specific for PDE4, we compared nine PDE inhibitors with different subtype selectivity: propentofylline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 59 publications
8
56
0
Order By: Relevance
“…Recent studies in rodent models have demonstrated decreased drinking behavior in animals given phosphodiesterase inhibitors (Hu et al, 2011;Wen et al, 2012;Blednov et al, 2014;Franklin et al, 2015). Together, these studies suggest that phosphodiesterase inhibition provides a promising target for the treatment of alcohol use disorders.…”
Section: Discussionmentioning
confidence: 89%
“…Recent studies in rodent models have demonstrated decreased drinking behavior in animals given phosphodiesterase inhibitors (Hu et al, 2011;Wen et al, 2012;Blednov et al, 2014;Franklin et al, 2015). Together, these studies suggest that phosphodiesterase inhibition provides a promising target for the treatment of alcohol use disorders.…”
Section: Discussionmentioning
confidence: 89%
“…Mice treated with either LV-Cre-EGFP or LV-EGFP-Empty were given continuous access to water and ascending concentrations of ethanol solutions (3%, 6%, 8%, 10%, 12%, 14%, and 16%, v/v) at 2 d intervals (Blednov et al, 2014). The position of administration tubes was changed daily to control for position preferences.…”
Section: Methodsmentioning
confidence: 99%
“…These drugs are thought to reduce inflammation by increasing cAMP concentration resulting in reduced NF-κB activation (Jimenez et al, 2001). Recently, these agents have been found to reduce ethanol intake in rodents (Bell et al, 2015; Blednov et al, 2014; Hu et al, 2011). A phase I clinical trial involving the PDE4 inhibitor ibudilast was recently completed but has not yet been reported.…”
Section: New Treatments Strategies Based On Immune Pharmacologymentioning
confidence: 99%